Passiflora gironensis a new species of Passiflora subgenus Astrophea (Passifloraceae) from Santander, Colombia - Aguirre-Morales, Adriana Carolina; Morales, Miguel Macgayver Bonilla; Rojas, Alicia (Phytotaxa, 2016)
Passiflora gironensis was found in the Interandean valley between Eastern and Central Cordillera, Department of Santander, Colombia, in a dry habitat. This is described, illustrated and placed in subgenus and supersection Astrophea section Capreolata. The new species is morphologically related to P. callistemma and P. ovata. P. gironensis, is an atypical species within sect. Capreolata because tendrils are absent and, as in P. callistemmma, flowers are paired or fasciculate. The new species differs from both those species by having more glands (6–8), longer pedicels (1.8–2.1 cm), longer sepals and petals (3.6–4.1 cm), fewer filaments of corona (3) and longer outer filaments (2.0–3.2 cm). In addition to the description of the new species, we include its distribution, ecology and conservation status.